2020
DOI: 10.1002/ccr3.3125
|View full text |Cite
|
Sign up to set email alerts
|

Bicipitoradial bursitis: A diagnosis challenge!

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The specific manifestations are a nodular slightly high signal on T2WI and fat suppression weighted, low signal on T1WI, and no enhancement after enhancement. However, compared to MRI, ultrasound examination is convenient, fast, cheap, and can obtain blood flow information, which is simpler and applicable in the follow-up of the disease, postoperative recurrence, and guiding puncture biopsy [9] . Therefore, in this case, we found that the patient did not undergo MRI, which is conducive to reducing the hospitalization cost of the patient, however we were still able to establish the presence of rice bodies in the tendon sheath by ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…The specific manifestations are a nodular slightly high signal on T2WI and fat suppression weighted, low signal on T1WI, and no enhancement after enhancement. However, compared to MRI, ultrasound examination is convenient, fast, cheap, and can obtain blood flow information, which is simpler and applicable in the follow-up of the disease, postoperative recurrence, and guiding puncture biopsy [9] . Therefore, in this case, we found that the patient did not undergo MRI, which is conducive to reducing the hospitalization cost of the patient, however we were still able to establish the presence of rice bodies in the tendon sheath by ultrasound.…”
Section: Discussionmentioning
confidence: 99%